Changes for Rebecca - Greene, Jacqueline Dembar; Hunt, Robert, 1952-; McAliley, Susan (Middleton, WI : American Girl, 2009)
Rebecca Rubin, the daughter of Russian Jewish immigrants in early twentieth-century New York, is appalled to see the horrible conditions at the factory where her friend Ana's brother and father work, and she is determined to do something to fix the problem, while keeping in mind how desperately the men need their jobs.
"American Girl"--Cover.
"1914."
4.6
3-6
Keywords: Sweatshops -- Juvenile fiction; Strikes and lockouts -- Juvenile fiction; Actors -- Juvenile fiction; Jews -- New York (State) -- New York -- Juvenile fiction; Family -- New York (State) -- New York -- Juvenile fiction; New York (N.Y.) -- History -- 20th century -- Juvenile fiction; Sweatshops -- Fiction; Strikes and lockouts -- Fiction; Actors and actresses -- Fiction; Jews -- New York (State) -- New York -- Fiction; Family life -- New York (State) -- New York -- Fiction; New York (N.Y.) -- History -- 20th century -- Fiction; Historical fiction; Sweatshops -- Fiction; Strikes -- Fiction; Actors -- Fiction; Jews -- New York (N.Y.) -- Fiction; Family life -- New York (N.Y.) -- Fiction; New York (N.Y.) -- History -- Fiction; Historical fiction; Historical fiction